On the spatial sensitivity of a 3D dosimetric phantom. (September 2016) - Apostolou, E.; Avgousti, R.; Armpilia, C.; Nikolakopoulou, A.; Zygogianni, A.; Antypas, C.
Abstract : Purpose: The aim of this study is to evaluate the spatial sensitivity of the 3D dosimetric phantom Delta 4 (Scandidos, Uppsala, Sweden) investigating whether phantom set up errors affect or not the measurement's results during plan verification. Materials and methods: The Delta 4 phantom is used to verify a test IMRT prostate plan that was created on Oncentra v4.3 (Nucletron, Electa) treatment planning system. The patient plan was transferred to the Delta 4 geometry and was delivered on a 6 MV photon beam SIEMENS Oncor Impression linac. The measurements' results are evaluated using the gamma index criteria (3%/3 mm) and the application of the plan is considered successful with an over 90% gamma index passing rate. The reference (no-shift) plan was delivered on the linac with a ±3 mm shift of the phantom at lateral, longitudinal and vertical direction. Results: The gamma index passing rate was measured at no-shift position 99.7%. For shifts in every direction gamma index was measured lower than 99.7% for each other position, but still over the passing rate limit 90%. The maximum and minimum gamma index passing rate for lateral direction was measured 96.7% (at +3 mm shift) and 89.6% (at −3 mm shift) respectively, for longitudinal direction 99.4% (at −3 mm shift) and 84.3% (at −3 mm shift) respectively and for vertical direction 96.2% (at −3 mm shift) and 88.7% (at −3 mm shift) respectively. Conclusion: In this study, the testing of the spatial sensitivity of Delta 4 phantom indicates that for 3%/3 mm gamma-index criteria the phantom lacks sensitivity for shifts less than 3 mm.